Surface Mining: Methods, Technologies and Systems. Volume-1 - Thompson, Roger (Wide Publishing, 2014)
Chapter 1: Failure Mechanisms on Rock Slopes and Slope Stability Analysis of Simple and Complex. Chapter 2: Error Reduction in Slope Stability Assessment 37. Chapter 3: Mining Waste Dumps 81. Chapter 4: Highwall Stability of Open Pit Mines 121. Chapter 5: The Effective use of Explosives in Mining 141. Chapter 6: Role of Delay Timing on Vibration Characteristics in Surface Mining Areas 169. Chapter 7: Electronic Detonators, Detonating Systems and Their Application 221. Chapter 8: Road-design and Road-safety in Surface Mining 251. Chapter 9: Customized Design and Selection of Continuous Mining Equipment in Surface Mines 269. Chapter 10: Water Management in Large Surface Mines 317. Chapter 11: Determining Waste Mining Rates of Open Pit Mines for Mine Planning and Design 355. Chapter 12: A New Era in Open Pit Mining: Mine-mill Integration and Enabling Technologies 373.